Mechanical Downsizing of a Gadolinium(III)-based Metal-Organic Framework for Anticancer Drug Delivery - Kundu, Tanay; Mitra, Shouvik; Patra, Prasun; Goswami, Arunava; Díaz Díaz, David; Banerjee, Rahul (Chemistry : a European journal, 2014)
A GdIII‐based porous metal–organic framework (MOF), Gd‐pDBI, has been synthesized using fluorescent linker pDBI (pDBI=(1,4‐bis(5‐carboxy‐1H‐benzimidazole‐2‐yl)benzene)), resulting in a three‐dimensional interpenetrated structure with a one‐dimensional open channel (1.9×1.2 nm) filled with hydrogen‐bonded water assemblies. Gd‐pDBI exhibits high thermal stability, porosity, excellent water stability, along with organic‐solvent and mild acid and base stability with retention of crystallinity. Gd‐pDBI was transformed to the nanoscale regime (ca. 140 nm) by mechanical grinding to yield MG‐Gd‐pDBI with excellent water dispersibility (>90 min), maintaining its porosity and crystallinity. In vitro and in vivo studies on MG‐Gd‐pDBI revealed its low blood toxicity and highest drug loading (12 wt %) of anticancer drug doxorubicin in MOFs reported to date with pH‐responsive cancer‐cell‐specific drug release. MOF nanocarrier: A new GdIII‐based porous metal–organic framework, Gd‐pDBI, with an elongated rotatable linker (DBI=(1,4‐bis(5‐carboxy‐1H‐benzimidazole‐2‐yl)benzene) was synthesized. Gd‐pDBI is biocompatible, water‐stable, and acid/base‐tolerant. Mechanical grinding yielded nanocrystals with excellent water dispersibility, and they feature the highest loading of the anticancer drug doxorubicin (DOX) and cancer‐cell‐specific drug release.